2018
DOI: 10.1016/j.margen.2018.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Genomic signatures of parasite-driven natural selection in north European Atlantic salmon (Salmo salar)

Abstract: Understanding the genomic basis of host-parasite adaptation is important for predicting the long-term viability of species and developing successful management practices. However, in wild populations, identifying specific signatures of parasite-driven selection often presents a challenge, as it is difficult to unravel the molecular signatures of selection driven by different, but correlated, environmental factors. Furthermore, separating parasite-mediated selection from similar signatures due to genetic drift … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 152 publications
0
30
0
Order By: Relevance
“…TA B L E 3 Regions with reduced heterozygosity in anadromous salmon. Listing regions showing consistently reduced heterozygosity in anadromous compared to landlocked populations (intersect of our data and the data from Zueva et al (2018)). Table 1 predominantly expressed in brain and gonads (Figures 2b and S4, File S2).…”
Section: Tissue-specific Gene Expression Of Genes In Selective Sweepsmentioning
confidence: 75%
See 3 more Smart Citations
“…TA B L E 3 Regions with reduced heterozygosity in anadromous salmon. Listing regions showing consistently reduced heterozygosity in anadromous compared to landlocked populations (intersect of our data and the data from Zueva et al (2018)). Table 1 predominantly expressed in brain and gonads (Figures 2b and S4, File S2).…”
Section: Tissue-specific Gene Expression Of Genes In Selective Sweepsmentioning
confidence: 75%
“…The x-axis shows the position in the genome, and the y-axis presents the difference in average heterozygosity (dZHp) between the two groups, where regions with low ZHp in landlocked salmon are present above 0 and regions with low ZHp in anadromous salmon are present below 0. Regions with consistently reduced heterozygosity in landlocked salmon that overlapped with any of the 28 selective sweeps are shown as yellow dots, and regions with consistently reduced heterozygosity in anadromous salmon (intersect of our data and data from Zueva et al (2018)) are shown as red dots. The regions highlighted by yellow and red dots are listed in Table 2 (in bold) and Table 3, respectively ,506,524-32,558,150 51,626 unknown, macf1, rft2 3 61,880,141-61,931,499 51,358 4 11,625,820-11,676,588 50,768 spcs3, wdr17, asb5 5 47,905,828-47,964,764 58,936 eif3e, rspo2 7 44,096,893-44,148,649 51,756 ppfia2 8 11,124,829-11,176,404 51,575 asb5, spcs3, wdr17 8 12,454,313-12,553,935 99,622 8 16,940,959-17,026,461 85,502 unknown, g3bp2, ppm1k, uso1, pkd2, abcg2 11 13,759,622-13,812,520 52,898 cadn 11 17,877,623-17,927,732 50,109 sbf2 14 25,660,660-25,712,400 51,740 tgfbr1 17 44,490,402-44,541,187 50,785 spic, bcl2l13, mybpc3 17 44,642,974-44,693,695 50,721 mch2, igf1, parpbp 27 161,241-236,092 74,851 psmd4, unknown, pip5k1a, znf687 Note:: Gene symbols of genes from the reference annotation are shown as obtained from the annotation against Swiss-Prot, where genes lacking a gene symbol are indicated by "unknown".…”
Section: Tissue-specific Gene Expression Of Genes In Selective Sweepsmentioning
confidence: 92%
See 2 more Smart Citations
“…In geographic areas in which founder effects and/or bottlenecks have led to a heterogeneous spatial distribution of alleles, parasite distribution could be spatially limited because of the presence of specific alleles conferring resistance (Zhang et al 2015, Charbonnel et al 2019). Next‐Generation Sequencing approaches have recently opened new research avenues by giving access to thousands of both non‐coding and coding markers related to host defense at the genome‐wide level (Wenzel et al 2015, Benavides et al 2016, Zueva et al 2018).…”
Section: Introductionmentioning
confidence: 99%